(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The idea of a virtual chorale, started by Eric Whittaker in 2009, was inspired by the virtual chorale that took place in the United Arab Emirates during the COVID-19 pandemic. This virtual chorale was successful due to the participation of precisely 117,572 singers from 129 countries. Due to its wide range of multiple benefits to an individual, researchers believe that singing is not the only thing that keeps people from participating in a chorale. However, recent studies have failed to demonstrate the benefits of choir participation in areas of self-esteem and involvement of an individual through social relationships as an individual’s overall development. The study aims to know the benefits of joining the chorale associated with the significant benefits in the areas of self-esteem and social relationships. The research objective is to determine the benefits it has on the respondents’ sense of self-belongingness, self- confidence, self-identity, and relationship with their immediate family, friends, and the community. The research supported the objective of the study of determining the benefits that the chorale has on the respondents’ sense of self-belongingness, self-confidence, self-identity, and relationship with their immediate family, friends, and the community. With the result acquired from the data, it was found that self-identity was the most beneficial component among other components of self-esteem and social relationships given in the study. After the research was conducted, this study concludes that there is a significant benefit on self-esteem and social relationships among the chorale members of Holy Family Parish. This study reveals that participating in a choir is highly beneficial to the self-esteem and social relationship involvement of the choir members.